Activity of MukBEF for chromosome management in E. coli and its inhibition by MatP - Seba, Mohammed; Boccard, Frederic; Duigou, Stéphane (eLife, 2024)
Structural maintenance of chromosomes (SMC) complexes share conserved structures and serve a common role in maintaining chromosome architecture. In the bacterium Escherichia coli, the SMC complex MukBEF is necessary for rapid growth and the accurate segregation and positioning of the chromosome, although the specific molecular mechanisms involved are still unknown. Here, we used a number of in vivo assays to reveal how MukBEF controls chromosome conformation and how the MatP/matS system prevents MukBEF activity. Our results indicate that the loading of MukBEF occurs preferentially on newly replicated DNA, at multiple loci on the chromosome where it can promote long-range contacts in cis even though MukBEF can promote long-range contacts in the absence of replication. Using Hi-C and ChIP-seq analyses in strains with rearranged chromosomes, the prevention of MukBEF activity increases with the number of matS sites and this effect likely results from the unloading of MukBEF by MatP. Altogether, our results reveal how MukBEF operates to control chromosome folding and segregation in E. coli.
Keywords: chromosome; MukBEF; MatP